Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: • Family Stability Among Families of Children with Autism Disorder: A Social Study (An Applied Study on Families of Children with Autism Disorder in the Regions of the Kingdom of Saudi Arabia – 2023 / 1444 AH) Ms. Albatool Houmeid Almalki, Ms. Ryouf Nasser Alkhaldi, Co-Prof. Rajaa Taha Alqahtani • Mothers’ Perspectives towards Factors Associated with Children’s Screen Time: An Analytical Cross-Sectional Study in the city of Jeddah Ms. Ruwaydah Abdulrahman Abdulwali, Co-Prof. Najat Abdullah Malibari • Coexistence and Tolerance in Granada during the Almoravid Era (448–541 AH / 1056–1147 AD) Dr. Maali Mohammed Yasin • Challenges Hindering the Utilization of Social Innovation Programs: A Study of the Reality of Social Work Pioneers. A descriptive study of enrollees in social innovation programs at Princess Al-Anoud Foundation, Riyadh, Kingdom of Saudi Arabia - May 2025 Ms. Maryam Saeed Almansouri, Co-Prof. Asma Mohammed Al-Bunyan • Researching China’s policy towards the sectarian conflict in Syria and its future Dr. Lao Linging • The Crisis of Party Action in Morocco and the Challenge of Fostering Development: An Analytical Study Dr. Fath Ellah Ramdani • The Use of Media in the Field of Da’wah: Between Reality and Prospects Co-Prof. Muhammad Aminul Hoque • L2 Morphology Acquisition Perspectives in Optimality Theory: Preliminary Observations of The Case of the Acquisition of the Past Tense Marker “-ed” Dr. Fehmi Youssef